Functional comparison of antisense proteins of HTLV-1 and HTLV-2 in viral pathogenesis - Barbeau, Benoit; Peloponese, Jean-Marie; Mesnard, Jean-Michel (Frontiers in Microbiology, 2013)
The production of antisense transcripts from the 3’ long terminal repeat (LTR) in human T-lymphotropic retroviruses has now been clearly demonstrated. After the identification of the antisense strand-encoded HTLV-1 bZIP (HBZ) factor, we reported that HBZ could interact with CREB transcription factors and consequently turn off the important activating potential of the viral Tax protein on HTLV-1 5’ LTR promoter activity. We have recently accumulated new results demonstrating that antisense transcripts also exist in HTLV-2, -3 and -4. Furthermore, our data have confirmed the existence of encoded proteins from these antisense transcripts (termed antisense proteins of HTLVs or APHs). APHs are also involved in the down-regulation of Tax-dependent viral transcription. In this review, we will focus on the different molecular mechanisms used by HBZ and APH-2 to control viral expression. While HBZ interacts with CREB through its basic zipper domain, APH-2 binds to this cellular factor through a five amino acid motif localized in its carboxyl terminus. Moreover, unlike APH-2, HBZ possesses an N-terminal activation domain that also contributes to the inhibition of the viral transcription by interacting with the KIX domain of p300/CBP. On the other hand, HBZ was found to induce T-cell proliferation while APH-2 was unable to promote such proliferation. Interestingly, HTLV-2 has not been causally linked to human T-cell leukemia, while HTLV-1 is responsible for the development of the Adult T-cell Leukemia/Lymphoma (ATLL). We will further discuss the possible role played by antisense proteins in the establishment of pathologies induced by viral infection.